Short steps long leaps : stories of impact making rural entrepreneurs - Awasthi, Dinesh N.; Awasthi, Dinesh N. (Dinesh Narain), 1948- (New Delhi ; New York : Tata McGraw Hill Pub. Co., 2001)
With reference to India; contributed articles.
Keywords: Small business -- India; Businesspeople -- India; Rural development -- India; Rural entrepreneur; Micro enterprise